Comics As Instructional Media in Education Journals Across Indonesia: A Systematic Literature Review - Noer Fitriyanti; Bachtiar Saiful Bahri; Andi Kristanto (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Comics with its features has the potential to increase motivations and creativity and the students' interest in understanding concepts. Educational comics is developed and utilized in classrooms. This systematic literature review analysis aims to focus on comics as instructional media in educational journals across Indonesia since 2018 to 2022. This current study has found that Research and Development is the most type of research employed to study educational comics. Relating to R and D method, ADDIE model has been most selected by researchers to develop educational comics. Elementary school students are the most chosen research subjects. Educational comics are utilized in Mathematics, natural science, Religion, Chemistry, Literacy, Thematic, Biology and English courses with particular topics. In addition, computer-based tools, web-based apps, and a combination of both are to develop educational comics in today's digital era.